Product Quality, Service Quality and Tupperware Brand Preference for Repurchase Interests - Ahmatang Ahmatang; Widya Surya Nigrum Widya; Dodi Apriadi Dodi Apriadi; Suryaningsih Suryaningsih (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This study aims to determine the effect of product quality, service quality, brand preference on the intention to repurchase Tupperware products in Tarakan City. A quantitative approach to the survey method was carried out in this study. The sampling method used was non-probability using a purposive sampling technique with the criteria being women using Tupperware products who had shopped for Tupperware products more than once. The sample in this study amounted to 180 respondents. In analyzing the data, using the analytical method consisting of Validity Test, Reliability Test, Classic Assumption Test, with processing using SPSS version 22. The results of this study indicate that product quality, service quality, brand preference have an effect on the intention to repurchase Tupperware products in Tarakan City